PENGARUH KOMPENSASI FINANSIAL, PROMOSI JABATAN TERHADAP KEPUASAN KERJA UNTUK MENINGKATKAN KINERJA PEGAWAI DI UNIVERSITAS JENDERAL SOEDIRMAN - Eko Sumanto; Wahyuningrat Wahyuningrat; Ali Rokhman (Program Magister Administrasi Publik, Fakultas Ilmu Sosial dan Politik, Universitas Jenderal Soedirman, 2016)
The performance of educational staff becomes an important element in the institution. Based on the previous research, it can be concluded that the level of user satisfaction either from students (external) or from employees within Unsoed (Internal) categorized at the level of quite satisfied. Therefore, more efforts need to be done in order to improve the performance of educational staff. The research model using analysis with the following hypotheses, H1: Financial compensation has positive effect on employee satisfaction, H2: Promotion has positive effect on employee satisfaction, H3: Financial compensation has positive effect on employee performance, H4: Promotion has positive effect on performance employees, and H5: job satisfaction has positive influence on employee performance. This research was conducted in Jenderal Soedirman University (Unsoed), using quantitative methods. The research target were all education personel in all unit in Unsoed with a total sample of 256 respondents. Data were collected using a questionnaire and then analysed using statistical analysis. The result from statistical analysis showed that the financial compensation were in a good category. Financial compensation has a significant influence on job satisfaction that is equal to 0.578. Promotion has been perceived as a good thing by the employees, and promotion has a significant influence on job satisfaction statistically which is equal to 0.545. Financial compensation has a significant influence on employee performance that is equal to 0.845. Promotion has a significant influence on employee performance that is equal to 0.680, statistically. The employees experienced a good job satisfaction, which encourage them to work better. Statistically, job satisfaction has a significant influence on employee performance that is equal to 0.730. The influence of financial compensation to the employees performance was increased from 49.9 percent to 69.5 after job satisfaction variables included as mediating variable. The result of sobel test confirmed that job satisfaction was capable to mediate the influence of financial compensation to the employee performance, significantly. The influence of promotion to employee performance was increased from 42 percent to 64.7 percent after included job satisfaction as mediating variable. Sobel test showed that that job satisfaction was capable to mediate the influence of promotion to employee performance, significantly. Keyword: Financial Compensation, Promotions, Job Satisfaction Staff Performance.